2016
DOI: 10.1111/ases.12334
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized controlled study on the validity and safety of an absorbable adhesion barrier (Interceed®) made of oxidized regenerated cellulose for laparoscopic colorectal surgery

Abstract: We have shown that using Interceed in laparoscopic colorectal surgery is valid and technically safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 9 publications
0
33
0
1
Order By: Relevance
“…Natural polymer based antiadhesives utilize materials such as hyaluronic acid, chitosan, and carboxymethylcellulose . A number of products showed good clinical results in abdominal surgery . Most natural polymer based products, however, are biomechanically weak and degrade too quickly to be used during tendon surgery.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural polymer based antiadhesives utilize materials such as hyaluronic acid, chitosan, and carboxymethylcellulose . A number of products showed good clinical results in abdominal surgery . Most natural polymer based products, however, are biomechanically weak and degrade too quickly to be used during tendon surgery.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…[28][29][30] A number of products showed good clinical results in abdominal surgery. [31][32][33] Most natural polymer based products, however, are biomechanically weak and degrade too quickly to be used during tendon surgery. Such limitations have led to research regarding decellularized tissue, which are both bioactive and biomechanically stronger than classic natural polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several products have been approved by European and United States authorities for use in abdominal and pelvic surgery, including Seprafilm® (hyaluronate carboxymethylcellulose), Interceed® (oxidised cellulose), Adept® (icodextrin 4%), Sprayshield™ (polyethylene glycol) and Hyalobarrier® (autocrosslinked polymers of hyaluronic acid). Although there was controversy regarding the safety of these products, new systematic reviews and clinical trials have demonstrated their safety but modest efficacy [ 63 , 65 67 ]. Recently, Seprafilm® has been shown to reduce adhesions in a randomised clinical trial including 30 patients who underwent open abdominal surgery [ 68 ].…”
Section: Battling Adhesionsmentioning
confidence: 99%
“…One of the first prototypes successful in reducing postoperative adhesions in humans was Interceed ® , which was composed of modified oxidized regenerated cellulose. This particular barrier was found to be applicable following gynecologic procedures; however, its efficacy in general surgical procedures is unknown [102]. Another type of biological barrier is expanded polytetrafluoroethylene (PTFE).…”
Section: Biological Barriersmentioning
confidence: 99%